Fabrication and characterization of oxide ion conducting films, Zr1−xMxO2−δ (M = Y, Sc) on porous SOFC anodes, prepared by electron beam physical vapor deposition. Issue 1 (3rd February 2017) - Shin, Tae Ho; Shin, Miyoung; Park, Geon-Woo; Lee, Shiwoo; Woo, Sang-Kuk; Yu, Jihaeng
Abstract : Fabrication of improved and easily controlled thin electrolytes for SOFCs via EB-PVD processing. Abstract : A key obstacle in reducing temperature loss is ohmic loss, which could be lowered by the use of thin electrolytes in electrochemical devices and thus various thin film processing methods have attracted much attention for applications in the SOFC market. Doped stabilized zirconia, Zr1− x M x O2− δ (M = Y, Sc), thin films were successfully deposited on a porous Ni-YSZ substrate via a commercial 10 kW EB-PVD system. The highly conductive and dense Zr1− x M x O2− δ (M = Y, Sc) thin films could be obtained by optimizing the distance (20–40 cm) between the substrate and target, angle (cos α, α = 0.19π–0.36π) for deposition area and substrate temperature (600–950 °C). Pseudo-cubic phase zirconia, with a preferential crystalline growth (111) and a unique columnar morphology, was observed with a fairly good value of conductivity; ScSZ and YSZ films had conductivities of 0.23 and 0.11 S cm −1 at 900 °C in air. This was achieved on the films which were prepared with proper geometric factors for physical deposition and with a substrate temperature of 950 °C. Finally, the YSZ and ScSZ electrolytes, prepared by EB-PVD, were applied on a solid oxide fuel cell with a Ni-YSZ anode and LSM cathode, which showed 1 W cm −2 of power density under 0.75 V at 900 °C.